Essential Oil Stocks Lotion FormulationBasil ( Ocimum Basilicum L. ) With CombinedStearic Acid As Carbopol 934 And WellAntibacterial Activity Of TestStaphylococcus Aureus - Rizki, Auliya Rahma, Dr. T.N. Saifullah S., M.Si., Apt, Ratna Yuliani, M. Biotech. St (2016)
Volatile oil of basil (Ocimum basilicum L.) containing linalool has antibacterial activity. Basil oil can be formulated in the form of lotion. The research aimed to know the influence of a thickener (carbopol 934) and anemulsifier (stearic acid) to the character properties physical, stability, and antibacterial activity of lotion containing volatile oil of basil againts Staphylococcus aureus. Four formulas of lotion with concentrations of carbopol 934 and stearic acid were prepared with ratio of 0.62:12.38 (F1), 0.48:9.52 (F2), 0.33:6.66 (F3), 0.19:3.81 (F4). Tests of properties physically and stability of lotion were done every month for 91 days include organoleptic test, viscosity, dispersive power, adhesion, pH, the size of the globules. Freeze-thaw cycling tests for 6 cycles were done to check organoleptic test, viscosity, and the size of the globules. Antibacterial activity against Staphylococcus aureus were conducted using well diffusion method. The analysis techniques used were non-parametric tests Kruskal-Wallis test followed by Mann-Whithney test or analysis of parametric one way ANOVA with LSD. Increasing concentrations of carbopol 934 and stearic acid increased the viscosity and adhesiveness of lotions significantly, but decreased dispersiveness significantly . The tests of lotion stability showed significant changes in the viscosity and dispersiveness during 3 months storage. Freeze-thaw cycling test (6 cycles) comprised the viscosity , globule size, and organoleptic showed significant changes in cycle 2. Lotion antibacterial activity decreased insignificantly during 91 days storage.